(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Automatic recognition of a person depends upon the physical or behavioral characteristics of an individual. Out of all characteristics like fingerprint, voice, face, keystrokes, the most popular method of identifying an individual is based on iris recognition. The most difficult step in iris recognition is the segmentation because it enhances and affects accuracy of matching the iris from database. Hough transform method is popular method for detection of circular features. As the iris and pupil are circular in shape, hough transform is used to locate the center of iris in image. The first step is acquisition of iris image, after that segmentation is done, feature extraction is done and finally iris image extracted is compared form database. In this paper, circular hough transform method was discussed and then comparative survey has been done on hough transform which is used by various researchers to localize iris image.